2007
DOI: 10.1017/cbo9780511546884
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Spanner Networks

Abstract: Aimed at an audience of researchers and graduate students in computational geometry and algorithm design, this book uses the Geometric Spanner Network Problem to showcase a number of useful algorithmic techniques, data structure strategies, and geometric analysis techniques with many applications, practical and theoretical. The authors present rigorous descriptions of the main algorithms and their analyses for different variations of the Geometric Spanner Network Problem. Though the basic ideas behind most of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
486
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 385 publications
(490 citation statements)
references
References 1 publication
1
486
0
3
Order By: Relevance
“…Since then, spanners have received a lot of attention; see the survey papers [10,13,22] and the books [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then, spanners have received a lot of attention; see the survey papers [10,13,22] and the books [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that for any set V of n points in the Euclidean space R d and for any fixed t > 1, the greedy spanner has O(n) edges, maximum degree O(1), and total weight O(wt(M ST (V ))), where wt(M ST (V )) is the weight of a minimum spanning tree of V ; see [8,18]. Thus, in R d , the naïve implementation of the greedy algorithm runs in near-cubic time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Euclidean spanners are being subject of ongoing intensive research since the mid-eighties. See the recent book by Narasimhan and Smid [19] for an excellent survey on this subject. Euclidean single-sink spanners were studied by Arya et al [2]; see also [19], Chapter 4.2.…”
Section: Rtvmentioning
confidence: 99%
“…See the recent book by Narasimhan and Smid [19] for an excellent survey on this subject. Euclidean single-sink spanners were studied by Arya et al [2]; see also [19], Chapter 4.2. Lukovszki [16,15] devised fault-tolerant constructions of single-sink spanners.…”
Section: Rtvmentioning
confidence: 99%